THE INFLUENCE OF DER, ROE ON DPR OF COMPANIES LISTED IN THE MES BUMN 17 INDEX - Widjiantoro, Surya Tegar; Segati, Ahda; Muda, Iskandar; Soemitra, Andri; Yusrizal (JSE: Jurnal Sharia Economica, 2025)
This study aims to analyze the effect of Debt- to-Equity Ratio (DER) and Return on Equity (ROE) on Dividend Payout Ratio (DPR) in companies listed in the MES BUMN 17 Index and also included in LQ45. The research employs a quantitative explanatory approach using panel data, with analysis conducted through EViews. The t-test results indicate that DER has a significant negative effect on DPR, while ROE is not significant. The F-test shows that DER and ROE simultaneously have a significant effect on DPR. The coefficient of determination (R²) of 0.260 reveals that most variations in DPR are influenced by other factors outside the model.